Strategic Insights for Environmental Education in Greece: SWOT and PEST Analyses in the Context of the Climate Change Crisis - Moshou, Hara; Hara Drinia (Sustainability, 2025)
Research on environmental education in Greece highlights the urgent need to integrate climate change education into school curricula due to the severe impacts of the climate crisis. Despite growing social awareness, implementation is hindered by limited resources resulting from the economic crisis, fragmented content in textbooks, and inadequate legislation. Technological advancements present new opportunities for enhancing environmental education. This article reviews the current state of environmental education and proposes strategic directions to improve its effectiveness. A SWOT analysis identifies internal strengths and weaknesses, along with external opportunities and threats, while a PEST analysis evaluates political, economic, social, and technological influences. Based on these assessments, strategic goals and directions are outlined, focusing on the comprehensive integration of Environmental Education for Climate Change into Greece’s compulsory education system. Key proposals include the development of clear policies, structured guidelines, and curriculum adaptations to address the evolving challenges of climate change. A cohesive national framework is recommended to ensure the consistent implementation of environmental education across all educational levels. These initiatives aim to prepare future generations with the necessary knowledge and skills to mitigate and adapt to climate change, fostering a more sustainable society.